Surface Roughness of CoCr and ZrO2 Femoral Heads with Metal Transfer: A Retrieval and Wear Simulator Study - Eberhardt, Alan W.; McKee, R. Travis; Cuckler, John M.; Peterson, Donald W.; Beck, Preston R.; Lemons, Jack E. (International Journal of Biomaterials, 2009)
Metal transfer to femoral heads may result from impingement against the metallic acetabular shell following subluxation/dislocation, or when metallic debris enters the articulation zone. Such transfers roughen the head surface, increasing polyethylene wear in total hip replacements. Presently, we examined the surface roughness of retrieved femoral heads with metallic transfer. Profilometry revealed roughness averages in regions of metal transfer averaging 0.380 μm for CoCr and 0.294 μm for ZrO2 which were one order of magnitude higher than those from non-implanted controls. Scanning electron microscopy (SEM) revealed adherent transfers on these retrievals, with titanium presence confirmed by electron dispersive spectroscopy. Due to the concern for increased wear, metal transfer was induced on non-implanted heads, which were then articulated against flat polyethylene discs in multidirectional sliding wear tests. Increased polyethylene wear was associated with these specimens as compared to unaltered controls. SEM imaging provided visual evidence that the transfers remained adherent following the wear tests. Pre- and post-test roughness averages exceeded 1 μm for both the CoCr and ZrO2 heads. Overall, these results suggest that metal transfer increases the surface roughness of CoCr and ZrO2 femoral heads and that the transfers may remain adherent following articulation against polyethylene, leading to increased polyethylene wear.